KALO AND SUGA: A Mobile Game On Awareness Of Calorie and Sugar Intake For Teenagers - Din, Suhaili; Mohomad Salehin, Luqman Hakim (Journal of Computing Technologies and Creative Content, 2020)
Calories and sugar is a nutrient that has been provided in almost foods. It is important for our body because calories give our body energy to do physical activity. Nowadays, most of the children are often live unhealthy life such as unhealthy eating habits and stay indoors. This has become a big concern as most of them may or had obesity-related diseases. This research purposes were to spread awareness of calories and sugar intake among teenagers using a mobile game application, and it will be developed in UNITY, and it only for an Android. This research use ADDIE MODEL for the research model. Online questionnaires were used to evaluate the effectiveness of the product in delivering awareness of calorie and sugar intake among teenagers. The results showed that the objective of this research has been achieved and this product gives knowledge and awareness of calorie and sugar intake among teenagers. This game also can help to promote a healthy lifestyle for the young generation.